2021
DOI: 10.3390/biom11081094
|View full text |Cite
|
Sign up to set email alerts
|

What Antarctic Plants Can Tell Us about Climate Changes: Temperature as a Driver for Metabolic Reprogramming

Abstract: Global warming is strongly affecting the maritime Antarctica climate and the consequent melting of perennial snow and ice covers resulted in increased colonization by plants. Colobanthus quitensis is a vascular plant highly adapted to the harsh environmental conditions of Antarctic Peninsula and understanding how the plant is responding to global warming is a new challenging target for modern cell physiology. To this aim, we performed differential proteomic analysis on C. quitensis plants grown in natural cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…It has been shown that carotenoids of the xanthophyll family and some other terpenoids bring about a decreased fluidity (thermostability) of the lipid membrane, resulting in reduced susceptibility to lipid peroxidation under high temperatures ( Havaux, 1998 ; Velikova et al, 2004 ; Sharkey, 2005 ). It is also worthwhile mentioning that in a recent paper it was demonstrated that plants grown under warmer conditions are able to better control oxidative stress and lipid peroxidation thanks to the activation of higher antioxidant defenses ( Bertini et al, 2021 ). Phenolics, flavonoids, anthocyanins, lignins, etc., are important secondary metabolites in plants and are involved in stress tolerance in the plant ( Chalker-Scott, 2002 ; Wahid, 2007 ; Wahid et al, 2007 ).…”
Section: Meta-analytic Review and Discussion On Plant Tolerance To Th...mentioning
confidence: 99%
“…It has been shown that carotenoids of the xanthophyll family and some other terpenoids bring about a decreased fluidity (thermostability) of the lipid membrane, resulting in reduced susceptibility to lipid peroxidation under high temperatures ( Havaux, 1998 ; Velikova et al, 2004 ; Sharkey, 2005 ). It is also worthwhile mentioning that in a recent paper it was demonstrated that plants grown under warmer conditions are able to better control oxidative stress and lipid peroxidation thanks to the activation of higher antioxidant defenses ( Bertini et al, 2021 ). Phenolics, flavonoids, anthocyanins, lignins, etc., are important secondary metabolites in plants and are involved in stress tolerance in the plant ( Chalker-Scott, 2002 ; Wahid, 2007 ; Wahid et al, 2007 ).…”
Section: Meta-analytic Review and Discussion On Plant Tolerance To Th...mentioning
confidence: 99%
“…Thus, Antarctic terrestrial plants are at the physiological limitations of survival. Consequently, bryophytes dominate the Antarctic land vegetation communities and only two vascular plants are present ( Cannone et al, 2016 ; Bertini et al, 2021 ). Since 1974 the depletion of stratospheric ozone over the Antarctic has led to enhanced UV-B radiation ( Rozema et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The powder was resuspended in 5 mL of a cold extraction buffer consisting of 50 mM sodium phosphate buffer (pH 7.5) including 1 mM EDTA, 1% (w/v) polyvinylpyrrolidone, 3 mM DTT, and a cocktail of protease inhibitors (Complete ULTRA tablets, Roche, Basel, Switzerland). The homogenate was centrifuged (Universal 32R, Hettich, Tuttlingen, Germany) at 9000 rpm for 15 min at 4 • C and the supernatant was used for enzyme activity assays as described in [77]. The protein content was estimated according to Bradford method using BSA as a standard.…”
Section: Protein Extractionmentioning
confidence: 99%
“…The level of TBARS was used to assess lipid peroxidation following the protocol described in [77]. Briefly, four hundred milligrams of frozen leaves were finely ground using a mortar and pestle under continuous addition of liquid nitrogen.…”
Section: Thiobarbituric Acid Reactive Substance Measurementmentioning
confidence: 99%